Analysis of Islamic Feminist Thought of Fatima Mernissi - Sonya Elsa Triyanda Pohan; Yusnaili Budianti; Azizah Hanum OK (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to: (1) describe the biography of Fatima Mernissi; (2) analyze Fatima Mernissi's Islamic feminist thoughts; and (3) examine the relevance of Fatima Mernissi's Islamic feminist thoughts in the context of contemporary Islamic education. The method used in this research is qualitative with a figure study approach that focuses on exploring the ideas, works, and contributions of Fatima Mernissi's thoughts to the discourse of Islamic feminism. Data were collected through a literature study of Mernissi's main works and relevant supporting literature. The results of the study show that: (1) Fatima Mernissi was born on September 27, 1940 in Fez, Morocco, and is known as a sociologist, writer, and Muslim feminist activist who critically examines the construction of patriarchy in social and religious traditions. (2) Mernissi's Islamic feminist thinking focuses on reinterpreting Islamic sacred texts and traditions to create a space for justice for women. She asserts that gender inequality often stems from biased interpretations of Islamic teachings, not from the teachings themselves. Through a sociological approach, Mernissi reveals how social and cultural structures contribute to the marginalization of women, while also encouraging women to play an active role in the process of interpreting religious texts and fighting for their rights within an egalitarian Islamic framework. (3) Mernissi's thoughts have significant relevance in contemporary Islamic education, particularly in efforts to achieve gender equality and women's empowerment through education. The idea can be implemented in the development of an Islamic education curriculum that is inclusive, dialogical, and responsive to gender issues, so that it can prepare a young generation that is just, critical, and adaptive to modern social dynamics from an Islamic perspective